2020
DOI: 10.1080/1359866x.2020.1849538
|View full text |Cite
|
Sign up to set email alerts
|

The potential of online technologies in meeting PLD needs of rural teachers

Abstract: In this paper we review the professional learning and development (PLD) needs of teachers in rural and remote schools, focusing on the Australian context. We argue that online PLD is an emerging alternative to face-to-face arrangements for the continuing education of teachers, which can connect to rural contexts through attending to considerations of relevance, collaboration, and future focus. We describe challenges to the uptake of online PLD initiatives and exemplify online PLD approaches with potential in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…1. The term 'digital' in this paper refers to web-based technologies for receiving and sending information and communicating through electronic devices (Meinokat and Wagner, 2021;Quinn et al, 2020). 2.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…1. The term 'digital' in this paper refers to web-based technologies for receiving and sending information and communicating through electronic devices (Meinokat and Wagner, 2021;Quinn et al, 2020). 2.…”
Section: Declaration Of Conflicting Interestsmentioning
confidence: 99%
“…Meanwhile, many researchers reported that teachers faced obstacles such as limited ICT literacy (Alea et al, 2020), juggling personal responsibilities, and being unable to properly manage time while working from home (Marimuthu & Vasudevan, 2020). Also, previous research showed that network connectivity issues (Savvidou, 2020), financial issues, other job scope conflicts (Badri et al, 2016), ineffective online PD design (Quinn et al, 2020), and unsatisfactory telecommuting using technologies (Alvarez, 2020) are among the barriers too.…”
Section: Literature Reviewmentioning
confidence: 99%